Disparity of Biofilm Formation in Salmonella typhimurium on Glass and Wood Surfaces at Diverse Incubation Temperatures - Sani Aliyu; Bello Usman (UMYU Journal of Microbiology Research)
Salmonella Typhimurium is a pathogenic gram-negative bacterium that commonly causes food- borne diseases known as gastroenteritis. Biofilm can exist on many surfaces in food preparation